W kręgu problematyki stosunków Kościoła i państwa w świecie późnego antyku - Leska, Alicja (Vox Patrum, 2018)
Alicja Leska in her article entitled On the range of problems concerning the relationship between the Church and the state in the late Antiquity outlines the way Christianity went from a persecuted religion to a state religion and demonstrates how Christianity changed the political and social relations in the Roman Empire completely and irretrievably. The Author indicates struggle and permeation of two worlds, pagan and Christian, during the economic crisis which started already in the 3rd century AD, barbarian invasions and migration of nations which intensified in the 5th century as well as the division of the Roman Empire. She presents arguments refuting the accusations of those historians who see the cause of Christianity’s victory in the ruin of the Roman Empire. Leska emphasizes it was a coincidence that the Church gained world importance at the time of the empire’s decline and fall into disorder. The Author points out that the Church, taking over the functions of the empire, was the only body able to manage the crisis of the West and assign meaning toit. Due to the unity and moral power and despite being shaken the same way like other institutions, the Church brought credit maintaining order and saving civilization.